A checklist of epibiont and parasite ciliates (Ciliophora) associated to rotifers (Rotifera) - Chatterjee, Tapas; Dovgal, Igor; Fontaneto, Diego; Zawal, Andrzej; Singh, Ravail (Zootaxa, 2023)
A review of the ciliate (Ciliophora) species associated to rotifers as epibionts and endoparasites is presented, based on published records. Thirty rotifer species from 12 genera are known as hosts of ciliates. Among ciliates, one species of class Suctorea and 14 species of class Oligohymenophorea (12 from subclass Peritrichia, one from Hymenostomatia, and one from Astomatia) have been noted as associated to rotifers. The possible factors responsible for host prevalence of ciliates are discussed.